2014
DOI: 10.1128/jvi.00317-14
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mosquito MicroRNA Aae-miR-2940-5p Is Downregulated in Response to West Nile Virus Infection To Restrict Viral Replication

Abstract: West Nile virus (WNV) is an enveloped virus with a single-stranded positive-sense RNA genome from the Flaviviridae family. WNV is spread by mosquitoes and able to infect humans, causing encephalitis and meningitis that can be fatal; it therefore presents a significant risk for human health. In insects, innate response to RNA virus infection mostly relies on RNA interference and JAK/SAT pathways; however, some evidence indicates that it can also involve microRNAs (miRNAs). miRNAs are small noncoding RNAs that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…Increased miR-2940-5p expression inhibited virus replication via suppression of a host metalloprotease, m41 FtsH, required for virus replication (32). In the current study, we investigated the role of host miRNAs in WNV KUN infection of human cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased miR-2940-5p expression inhibited virus replication via suppression of a host metalloprotease, m41 FtsH, required for virus replication (32). In the current study, we investigated the role of host miRNAs in WNV KUN infection of human cells.…”
mentioning
confidence: 99%
“…Previously, we demonstrated that the host response against WNV KUN in mosquito cells involves the downregulation of the miRNA aae-miR-2940-5p, which is required for viral replication (32). Increased miR-2940-5p expression inhibited virus replication via suppression of a host metalloprotease, m41 FtsH, required for virus replication (32).…”
mentioning
confidence: 99%
“…A target of aaemiR-2940-5p is the metalloprotease m41 FtsH gene (MetP), which is positively regulated by the miRNA [39]. Interestingly, MetP was found to enhance WNV replication [38 ]. Therefore, reduction of aae-miR-2940-5p abundance after WNV infection leads to lower MetP levels in the cell resulting in reduced virus replication.…”
Section: Cellular Mirnas Targeting Viral or Host Genesmentioning
confidence: 99%
“…Given that other cellular miRNAs tested were not affected, the decline in aae-miR-2940 is not due to a global decline in miRNA biogenesis but a selective response. This suggested a miRNA-dependent antiviral response to limit viral replication [38 ].…”
Section: Cellular Mirnas Targeting Viral or Host Genesmentioning
confidence: 99%
See 1 more Smart Citation